2020
DOI: 10.1002/jbmr.4026
|View full text |Cite
|
Sign up to set email alerts
|

The Women's Health Initiative: A Landmark Resource for Skeletal Research Since 1992

Abstract: The Women's Health Initiative (WHI) is a large longitudinal study designed to investigate strategies for the prevention and control of common chronic diseases in postmenopausal women, including cardiovascular disease, cancer, and osteoporotic fractures. The WHI consisted of three overlapping clinical trials of hormone therapy, diet modification to reduce total dietary fat, and calcium/vitamin D supplementation. Women who were ineligible for the hormone therapy or diet modification trials or not interested were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Recruitment included mailings to 71,521 active Women's Health Initiative (WHI) Extension Study participants ( 37 ) and mailings by Brigham and Women's Hospital (BWH) to 237,736 women and men contacted for, but not randomly assigned to, the VITamin D and OmegA-3 TriaL (VITAL) ( 38 ); mass mailings to 2,616,343 US men and women; and mailings to 3380 volunteers through other sources, including responses to media stories and advertisements. Of 191,796 participants completing a brief screening questionnaire, 120,629 were initially eligible and willing; then 63,025 completed another questionnaire with written informed consent before enrollment with oversight by the Human Subjects Committee at BWH.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment included mailings to 71,521 active Women's Health Initiative (WHI) Extension Study participants ( 37 ) and mailings by Brigham and Women's Hospital (BWH) to 237,736 women and men contacted for, but not randomly assigned to, the VITamin D and OmegA-3 TriaL (VITAL) ( 38 ); mass mailings to 2,616,343 US men and women; and mailings to 3380 volunteers through other sources, including responses to media stories and advertisements. Of 191,796 participants completing a brief screening questionnaire, 120,629 were initially eligible and willing; then 63,025 completed another questionnaire with written informed consent before enrollment with oversight by the Human Subjects Committee at BWH.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, an embedded recruitment approach was conducted from June 2015 to March 2018 with mailings to active participants in the Women's Health Initiative (WHI) Extension Study ( 33 ), mailings by Brigham and Women's Hospital (BWH) to women and men contacted for but not randomly assigned to the VITamin D and OmegA-3 TriaL (VITAL) ( 34 ), mass mailings, and mailings to volunteers who heard about the study through various sources ( Supplementary Methods ). To be eligible, participants agreed to forego personal MVM and cocoa extract supplement use during the trial, limit vitamin D to ≤1000 IU/d and calcium to ≤1200 mg/d from all supplemental sources, and complete at least a 2-mo placebo run-in phase taking ≥75% of the study pills.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, WHI is a large-scale prospective study of postmenopausal women, aged 50–79 at baseline, who were enrolled at 40 clinical centers throughout the United States between 1993 and 1998. The main WHI study concluded in 2005; follow-up of surviving participants is ongoing in WHI Extension Studies ( 16 ). The WHI study involves both an observational study (OS) arm and three overlapping randomized trials.…”
Section: Methodsmentioning
confidence: 99%